Find the solution of 3^{4x} = 9^{(x-1)/2}.

First, recognise that 3^2 = 9. Recall the rule for multiplying indices, that (a^b)^c = a^{bc}. Then, substitute 3^2 in place of 9 to get 3^{4x} = (3^2)^{(x-1)/2}. Use the rule for multiplying indices, so that the equation is now 3^{4x} = 3^{x-1}. This implies 4x=x-1, and therefore 3x = -1, and finally, x = -1/3 is the solution.

Related Further Mathematics GCSE answers

All answers ▸

Differentiate y = x*cos(2x)


A curve has equation y = ax^2 + 3x, when x= -1, the gradient of the curve is -5. Work out the value of a.


A curve has equation: y = x^3 - 3x^2 + 5. Show that the curve has a minimum point when x = 2.


Why is it that when 'transformation A' is followed by 'transformation B', that the combined transformation is BA and not AB?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences